Dietary Supplementation of Chromium Picolinate on Productive Performance and Cost Economics of Coloured Broiler Chicken during Hot-Humid Summer - Kulkari, R. C.; Mandal, A. B.; Bhanja, S. K.; Goel , Akshat; Mehera, Manish (International Journal of Livestock Research, 2018)
The efficacy of chromium picolinate (0, 20 or 40 mg/kg diet) in coloured broilers (n=120) was evaluated (0-42 d) during hot-humid summer. The chicks were randomly divided into three treatment groups having five replicate of eight birds each. The parameters viz. feed intake, body weight gain, feed conversion ratio, energy and protein efficiency, carcass traits, immune-competence and cost economics were studied. The 0-42 d body weight gain and feed intake was comparable with improved FCR. There was no significant difference in the yield of breast, back, drumstick, thigh, neck and wing. The supplementation of Cr picolinate did not bring any significant changes in the shrinkage, blood and feather loss, but eviscerated and ready to cook yield improved significantly with fat pad reduction. The cost/kg live weight and cost/kg meat yield were reduced. Dietary addition of 20 mg chromium picolinate per kg diet helps to improve the production performance.